Accurate measurement of microscopic forces and torques using optical tweezers - Melanie McLaren; Elias Sidderas-Haddad; Andrew Forbes (South African Journal of Science)
It is now well known that matter may be trapped by optical fields with high intensity gradients. Once trapped, it is then possible to manipulate microscopic particles using such optical fields, in so-called optical tweezers. Such optical trapping and tweezing systems have found widespread application across diverse fields in science, from applied biology to fundamental physics. In this article we outline the design and construction of an optical trapping and tweezing system, and show how the resulting interaction of the laser light with microscopic particles may be understood in terms of the transfer of linear and angular momentum of light. We demonstrate experimentally the use of our optical tweezing configuration for the measurement of microscopic forces and torques. In particular, we make use of digital holography to create so-called vortex laser beams, capable of transferring orbital angular momentum to particles. The use of such novel laser beams in an optical trapping and tweezing set-up allows for the control of biological species at the single-cell level.